Analysis of the interactome of ribosomal protein S19 mutants. Issue 20 (18th September 2014) - Caterino, Marianna; Aspesi, Anna; Pavesi, Elisa; Imperlini, Esther; Pagnozzi, Daniela; Ingenito, Laura; Santoro, Claudio; Dianzani, Irma; Ruoppolo, Margherita
<x xml:space="preserve">Abstract</x> Diamond–Blackfan anemia, characterized by defective erythroid progenitor maturation, is caused in one‐fourth of cases by mutations of ribosomal protein S19 (RPS19), which is a component of the ribosomal 40S subunit. Our previous work described proteins interacting with RPS19 with the aim to determine its functions. Here, two RPS19 mutants, R62W and R101H, have been selected to compare their interactomes versus the wild‐type protein one, using the same functional proteomic approach that we employed to characterize RPS19 interactome. Mutations R62W and R101H impair RPS19 ability to associate with the ribosome. Results presented in this paper highlight the striking differences between the interactomes of wild‐type and mutant RPS19 proteins. In particular, mutations abolish interactions with proteins having splicing, translational and helicase activity, thus confirming the role of RPS19 in RNA processing/metabolism and translational control. The data have been deposited to the ProteomeXchange with identifier PXD000640 (http://proteomecentral.proteomexchange.org/dataset/PXD000640).